Surface-spreading technique of meiotic cells and immunodetection of synaptonemal complex proteins in teleostean fishes - Araya-Jaime, Cristian [UNESP]; Serrano, Erica Alves [UNESP]; Zerbinato de Andrade Silva, Duilio Mazzoni [UNESP]; Yamashita, Masakane; Iwai, Toshiharu; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Biomed Central Ltd, 2015)
Background: Different moderrn methodologies are presently available to analyze meiotic chromosomes. These methods permit investigation of the behavior of chromosomes in the normal complement and of sex and B chromosomes, two special types of chromosomes that are associated with the A complement and are present in many organisms, including fishes. However, meiotic studies are still scarce in fishes, considering the wide number of species in this group.. Here, we describe a new protocol for the visualization of the synaptonemal complex in spermatocytes and oocytes of fishes and to the sequential use of the technique with other procedures and techniques such as immunodetection of the synaptonemal complex protein with a specific antibody and co-detection of DNA sequences by FISH.Results: The meiotic surface-spreading protocol used in the present proposal worked well in representative species of four fish orders and was useful in obtaining good results even in small specimens. Fish-specific antibodies and commercial products worked similarly well to detect synaptonemal complex (SC) proteins. The sequential application of fluorescence in situ hybridization using specific probes showed clear signals associated with the SC structures identified by immunostaining.Conclusion: Here, we provide a useful and applicable immunofluorescent protocol for the visualization of synaptonemal complex proteins in the meiotic cells of fishes in surface-spreading preparations. Furthermore, this technique allows for the sequential application of other cytogenetic procedures.
Keywords: Meiosis; SYCP3; Method; Co-detection; FISH